The invisible burden of managing COVID-19 for Australian women: Cognitive labor and public health information - Lee, Ashlin; Kakoschke, Naomi; Higgins, Liesel; Reeson, Andrew; Brindal, Emily (Frontiers in Public Health, 2023)
Providing accurate and timely public health information is an ongoing challenge for public health officials. The COVID-19 pandemic has exacerbated such challenges and presented unique difficulties in providing public health information, through the parallel rise of an “infodemic” of mis/dis-information. Understanding why individuals select, use and change their public health information seeking behaviors around COVID-19, and the relationship of these decisions relative to participant characteristics, is therefore an important step in understanding and responding to infodemics. This study used a qualitative survey (n = 255) and free-text qualitative questions to ask (1) Why participants use an information source, (2) How participants used an information source, and (3) How information seeking behavior has changed since the COVID-19 pandemic. Participants were primarily women, born in Australia, with de-facto/married relationships, without children at home, with university/college qualifications, and employed full-time or unemployed/retired. Most participants identified “easiness” and “immediacy” as reasons why they chose and used information, with sources primarily used for planning, communication, and decision making. A minority of participants changed their information seeking behavior since the COVID-19 pandemic. Those who did change, desired more immediate and accurate information. Emergent themes of care and anxiety were also noted, raising questions around the impact of mental load and cognitive labor in some female populations. Women may be suffering from increased cognitive labor and a gendering of public health information seeking behavior in the context of COVID-19. The impact of these attributes on women requires greater empirical research and consideration amongst front line practitioners and public health professionals.